Salmonella enterica Serotype Typhimurium DT 104 Antibiotic Resistance Genomic Island I in Serotype Paratyphi B - Meunier, Danièle (Centers for Disease Control and Prevention, 2002)
We have identified Salmonella genomic island I (SGI1) in an isolate of Salmonella enterica serotype Paratyphi B. This antibiotic-resistance gene cluster, which confers multidrug resistance, has been previously identified in S. enterica serotype Typhimurium phage types DT 104 and DT 120 and in S. enterica serotype Agona.